Application of MBR Technology in Landfill Leachate Treatment - ZHONG Zhaohuang; LI Xindong; LI Haike; OUYANG Guozi; LI Lang; CAI Meng (Renmin Zhujiang)
This paper analyzes the sources and water quality characteristics of landfill leachate and compares the commonly used treatment technologies of landfill leachate both at home and abroad.In addition,the applications of combined processes with MBR technology at the core in landfill leachate are introduced in detail,including anaerobic membrane bioreactor (AnMBR) technology,anaerobic biological treatment+MBR technology,physicochemical treatment+MBR technology,and the coupling of MBR and NF/RO membrane.Finally,the development trend of MBR technology in landfill leachate treatment is analyzed.